A Study of Economic Driven Sectors to Increase the Domestic and Foreign Investment - Veggy Anugrah Sasmita; Ade Wahyudi; Faizan Dalilla (International Journal Labs, 2023)
Bengkalis regency rank first in the domestic and foreign investment in Riau Province in 2021. However, along with the economic growth, the initial potential sectors such as mining and excavation showed a significant decrease between 2017 and 2020. Meanwhile, the mining and excavation sector used to be the biggest contribution to the economic development of Bengkalis. This research aims to analyze the driving sectors in raising the domestic and foreign investment in Bengkalis Regency. The research is an explanatory research to explain the relationship and influence of research variables in the GRDP sector on domestic investment and foreign capital. The analysis used multiple regression by SPSS software and regional economic analyses. The result indicated that the domestic investment is affected by secondary sectors, while the foreign investment is affected by the secondary and tertiary sectors.